GOOD PRACTICES OF HYBRID STATE-OWNED ENTERPRISES LISTED ON THE WARSAW STOCK EXCHANGE - Kreczmańska-Gigol, Katarzyna; Gigol, Tomasz (Management and Administration Journal, 2024)
State-owned enterprises play a major role in today’s global economy. However, they are accused of low efficiency as a result of flawed corporate governance. Listed state-owned enterprises are hybrid companies because they combine different institutional logics. Listed companies, in order to gain legitimacy from stakeholders, provide information to the market. Stakeholders expect companies to provide reliable information on the achievement of goals they care about. Corporate governance is monitored on reports of listed companies’ adherence to good practices of listed companies. It was decided to investigate the usefulness for stakeholders of reports on compliance with the good practice of companies on the Warsaw Stock Exchange for assessing corporate governance. Corporate governance is a problem for state-owned enterprises due to the need to combine corporate and state logic. Hybrid state-owned enterprises (SOEs) also have to follow the logic of the capital market. Therefore, the subject of the study was compliance with good practices of listed companies by hybrid SOEs listed on the Warsaw Stock Exchange. The aim of the study was to find out how their corporate governance compares with other companies. A quantitative study was conducted using the COMPLY factor. It turned out that hybrid SOEs performed better than other companies listed on the same stock indices and in the same sectors. Thus, the results of the study point to the inadequacy of the good practice reporting system.